IDENTIFIKASI CEMARAN Salmonella sp. PADA AYAM POTONG DENGAN METODE KUANTIFIKASI DI TIGA PASAR TRADISIONAL DAN DUA PASAR MODERN DI KOTA BANDAR LAMPUNG [Identification of Salmonella Sp. Contamination on Broilers with Quantification Method at Three Traditional Markets and Two Modern Markets in Bandar Lampung] - Sartika, Dewi; Susilawati, Susilawati; Arfani, Gusman (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
Salmonella sp. is a bacteri that causes of contamination on broilers and salmonellosis in humans. The acording of SNI 7388 (2009), chicken meat safety for comsumption is must be negative Salmonella sp content. The porpuse of this research was to identify Salmonella sp. contamination on boilers at traditional market and modern market in Bandar Lampung. This research used samples of chicken meat from 3 traditional markets (Gintung Market, Rajabasa Market and Tamin Market) and 2 modern markets (Robinson Super Market and Chandra Super Market). All of samples were isolated on to selective media Xylose Lysine Desoxycholate (XLD) agar with 3 replication. The result showed that contamination of SalmonellIa sp. was identified on boilers at traditional market and modern market with the contamination level on Gintung Market was 4,80x108 CFU/g – 2,48 x109 CFU/g, Rajabasa Market was 3,68x108 CFU/g, - 1,24x109 CFU/g, Tamin Market was 3,30x108 CFU/g – 3,68x109 CFU/g, Robinson Super Market was 3,27x104 CFU/g – 1,50x105 CFU/g and Chandra Super Market was 3,30x104 CFU/g – 1,13x105 CFU/g. The conclusion was this research was the contamination level at traditional markets was higher then the modern markets.Keywords: broilers, contamination, modern market, Salmonella sp., traditional market.